Comparison of Neuromuscular Blockade with Two Different Agents After A Priming Dose of Rocuronium: A Randomized Clinical Trial. - Sen, Betül; Güra, Melek (Turkiye Klinikleri Journal of Medical Sciences, 2012)
ABS TRACT Ob jec ti ve: The pur po se of this study was to as sess the phar ma co lo gi cal ef fects of a pri ming do - se of ro cu ro ni um in com bi na ti on with the non-de po la ri zing bloc kers ro cu ro ni um or ve cu ro ni um du ring the pe ri o pe ra ti ve pe ri od. Ma te ri al and Met hods: Sixty pa ti ents with Ame ri can So ci ety of Anest he si o lo gists (ASA) risk sta tus I or II sche du led to re ce i ve anest he si a for elec ti ve sur gery we re inc lu ded in the study. Pati ents we re ran domly di vi ded in to fo ur gro ups. Pa ti ents in Gro up I (n=15) re ce i ved a pri ming do se of normal sa li ne and ro cu ro ni um bro mi de 0.6 mg/kg fol lo wing in duc ti on of anest he si a; pa ti ents in Gro up II (n=15) re ce i ved a pri ming do se of nor mal sa li ne and ve cu ro ni um bro mi de 0.1 mg/kg fol lo wing in duc ti on; pa ti ents in Gro up III (n=15) re ce i ved a pri ming do se of ro cu ro ni um bro mi de 0.1 mg/kg fol lo wed by ro cu ro ni um bro mi de 0.6 mg/kg af ter in duc ti on; and Gro up IV (n=15) pa ti ents re ce i ved a pri ming do se of ro cu ro ni um bro mi de 0.1 mg/kg fol lo wed by ve cu ro ni um bro mi de 0,1 mg/kg. T95 (ti me to on set of ac ti on), T25 (cli ni - cal du ra ti on of ac ti on), T75 (to tal du ra ti on of ac ti on) and re co very in dex (RI) we re me a su red and re cor ded. Pa ti ents we re mo ni to red for pos sib le si de ef fects. Re sults: In Gro up II I, in which pa ti ents we re pri med with ro cu ro ni um and ma in ta i ned with ro cu ro ni um, the ti me to on set of ac ti on was sig ni fi cantly shor ter than for pa ti ents in Gro up I. Si mi larly, this pa ra me ter was sig ni fi cantly shor ter in Gro up IV pa ti ents than in Gro up II pa ti ents. T25 and T75 was sig ni fi cantly lon ger in Gro up II and Gro up IV than in the ot her gro ups. The - re was no sig ni fi cant dif fe ren ce in RI va lu es bet we en the gro ups. Conc lu si on: Using ro cu ro ni um as a pri - ming agent ac ce le ra tes the ne u ro mus cu lar bloc king ef fects of both ro cu ro ni um and ve cu ro ni um and pro vi des ide al in tu ba ti on con di ti ons when sa fe and qu ick in tu ba ti on is re qu i red.